Role of miR-21 on vascular endothelial cells in the protective effect of renal delayed ischemic preconditioning - Xu, Xialian (Mol Med Rep, 2017)
Vascular endothelial cells may serve crucial roles in the development of acute kidney injury (AKI). microRNA (miR)-21, which possesses a renal protective function has been found on vascular endothelial cells. The present study aimed to test the hypothesis that miR-21 may protect vascular endothelial cells against injury, which may contribute to the protective effects of renal delayed ischemic preconditioning (IPC). Preconditioned (15 min ischemia) or Sham mice (not clamped) were subjected to 35 min occlusion of bilateral renal pedicles 4 days following preconditioning or Sham treatment. Human umbilical vein endothelial cells (HUVECs) were treated with cobalt(II) chloride (CoCl2) to establish an in vitro hypoxia model. Locked nucleic acid-modified anti-miR-21 or scrambled control oligonucleotides were transfected into cells or delivered into mice via tail vein injection <1 h prior to IPC. Following 24 h of reperfusion or hypoxia, morphological and functional parameters, apoptosis and miR-21 and programmed cell death 4 (PDCD4) expression were assessed in vivo and in vitro. Treatment of HUVECs with CoCl2 led to an upregulation of miR-21 expression, a downregulation of PDCD4 protein expression and attenuation of apoptosis. Inhibition of miR-21 expression led to increased expression levels of PDCD4 protein and apoptosis in HUVECs. IPC attenuated renal IR injury in mice. The protective effect of IPC appeared to be dependent on upregulated miR-21 expression. IPC-induced upregulation of miR-21 expression also occurred in HUVECs, and IPC also led to reduced PDCD4 expression and vascular permeability in mouse kidneys. The effects of IPC were attenuated by the inhibition of miR-21; miR-21 expression attenuated damage in vascular endothelial cells, which may contribute to the protective effects of delayed IPC on renal IR injury. The present study suggested a novel target for the prevention and repair of AKI in the future.